Integrating management systems in the energy sector: the case of the electricity industry in New Zealand - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
The New Zealand Electricity Engineers Association (EEA) asked for advice about development of a guide for a public safety management system (PSMS) for electricity distribution networks based on ISO45001 Occupational health and safety management systems. This would help eliminate overlap between legislation and standards while maintaining compliance with legal requirements. At Victoria University of Wellington we have been working on such an integrated approach and this article reports on the project and suggests how the results can be extended to include other areas of management while retaining the ability for appropriate elements to be audited and certified in accordance with systems required by legislation. The project reviewed an earlier report and literature review on PSMS for the Electricity Networks Association. Development of the legal requirements for a PSMS were reviewed and use of the International Standards Organization (ISO) framework for all management system standards proposed to encompass ISO45001 and similar standards. Relevant management content was incorporated in the high-level structure and key stakeholders contributed technical content. Use of the ISO Annex SL as a template enabled development of an integrated management system incorporating other management system standards, that would still support legal compliance while enabling elimination of duplication and clutter, and waste of resources at a time of technology change. The work was carried out in New Zealand (NZ) and may not apply in other countries with different legal requirements. Auditors may resist integrated management systems although this may not be a limitation if documentation is appropriately written. The electricity networks businesses in NZ may move to implementation of the PSMS guide but this will be an internal decision and results may take some years to declutter documentation and reduce overlapping audits under management system standards. Over the next decade the context of the New Zealand electricity industry will undergo major shifts with the need to adapt to increasing expectations for occupational health and safety and public safety, adaptation to climate change and accelerated implementation of new technologies. The electricity industry will need to apply its resources to those changes while avoiding duplicated efforts to implement multiple management systems. Developing an integrated management system that incorporates several management systems and public safety may aid protection of non-workers who cannot otherwise be “controlled” by a business.